Sexual dimorphism in the immune response of Drosophila melanogaster to the entomopathogenic fungus Metarhizium anisopliae. - Peng, Y.; Lyu, J.; Li, Q.; Ligoxygakis, P.; Xia, Y.; Xiao, Q. (Journal of Invertebrate Pathology, 2025)
The immune response of insects to pathogenic micro-organisms infection usually exhibits significant sex differences. Understanding this sexual dimorphism elucidates how immunity interplays with reproductive strategy, metabolic status and environmental factors. In this study, we showed female Drosophila melanogaster (fruit fly) survived better than males when infected with Metarhizium anisopliae CQMa421. This sex-specific survival difference depends on the Toll pathway, which is critical for innate immunity. We systematically compared innate immunity, including humoral immunity, cellular immunity, and melanization, between infected male and female flies. Female flies displayed a faster humoral immune response, characterized by earlier upregulation of antimicrobial peptides (AMPs) expression in both fat body and gut. On the other hand, male flies exhibited a stronger early cellular immune response, marked by increased expression of genes associated with hemocyte clotting and phagocytosis. While male flies upregulated melanization related Prophenoloxidase (PPO) earlier than female flies, both sexes significantly increased phenoloxidase (PO) activity after fungal infection. Fungal load quantification revealed that CQMa421 proliferated more quickly in females than in males. Collectively, our data indicate that each sex exhibits advantages in specific immune response, and that sex-biased survival outcome arises from the integration of multiple host defense mechanisms.